Marital Status and Support for Women's and Children's Wellbeing: Perspectives of Rural Ghanaian Women (P04-038-19). (13th June 2019) - Dallmann, Diana; Marquis, Grace; Colecraft, Esi; Dodoo, Naa; Addy, Nii
Abstract: Objectives: Cohabiting but previously divorced women may be at increased risk of food insecurity. This study explored women's perceptions of how current and prior marital status could influence food security status. Methods: Nine focus group (FG) discussions were held with mothers of young children who participated in a nutrition-sensitive agriculture intervention (Nutrition Links) in rural Ghana. Nine of 13 intervention communities were purposively selected to participate. Each FG had 5 to 9 women who were asked about the support they received from their partners regarding food for the household, entrepreneurship activities, and their children's healthcare. How this support changed with marital status, and from where else women could get support was further probed. Translated transcriptions of FG were thematically analyzed. Results: Most women reported that men helped with money for food for the household or food stuff from farm. Divorced women would not receive that kind of support. The only support women agreed that men provided independent of marital status was for children's healthcare. Often, the main support network women counted on was that of their immediate family. Co-habiting women would be "pampered" by their partners. However, they would receive little support to develop their own business because men feared that a woman might leave if she were successful. FG participants complained about the lack of freedom married women had, but most of them agreed that married women had a better economic and social standing and had more support from their husband's family than non-married women. FG women reported that married men were more likely to support their wives' business - assuming that they would also benefit - but a man would hinder his wife's entrepreneurial growth out of jealousy if he perceived that she was moving ahead of him. Conclusions: Marital status might affect the support women receive for food security in complex ways. Divorced women do not receive economic support from their ex-husbands and cohabiting women do not receive support to develop their business. As previous studies suggested, focusing solely on female household headship might not be enough to identify the most vulnerable individuals. Thus, interventions and policies targeting maternal and child nutrition should consider women's marital status as well as their support networks. Funding Sources: International Development Research Centre (IDRC) Global Affairs Canada McGill University World Vision University of Ghana